Balanophora polyandra Griff. prevents dextran sulfate sodium-induced murine experimental colitis via the regulation of NF-κB and NLRP3 inflammasome. Issue 7 (23rd June 2020) - Guo, Chong; He, Yumin; Gai, Liyue; Qu, Jiayuan; Shi, Yue; Xu, Wen; Cai, Yuxuan; Wang, Bei; Zhang, Jiali; Zhao, Zongyao; Yuan, Chengfu
Abstract : Balanophora polyandra Griff. ( B. polyandra ) is a folk medicine used as an antipyretic, antidote, haemostatic, dressing and haematic tonic, for the treatment of gonorrhea, syphilis, wounds, and the bleeding of the alimentary tract by the local people in China. Abstract : Balanophora polyandra Griff. ( B. polyandra ) is a folk medicine used as an antipyretic, antidote, haemostatic, dressing and haematic tonic, for the treatment of gonorrhea, syphilis, wounds, and the bleeding of the alimentary tract by the local people in China. This study was designed to investigate the effects of B. polyandra on dextran sulfate sodium (DSS)-treated colitis mice in vivo and lipopolysaccharide (LPS)-induced RAW 264.7 macrophages in vitro . Mice were induced with B. polyandra total extract (BPE, 250 and 1000 mg kg −1 ) and B. polyandra polysaccharides (BPP, 100 and 400 mg kg −1 ) for 22 days and treated with 3.5% DSS in their drinking water for the last 7 days and the LPS-induced RAW264.7 macrophages were treated with BPE (100 μg ml −1 ) and BPP (100 μg ml −1 ). Mice treated with DSS developed severe mucosal colitis, with a marked distortion and crypt loss of colonic surface epithelium and a colonic shortening. B. polyandra significantly inhibited colonic shortening and reduced the severity of colitis in the colon and lowered the colonic inflammation score ( p < 0.05) and decreased the expression of interleukin (IL)-1β, tumor necrosis factor (TNF-α), inducible nitric oxide synthase (iNOS), and anti-serum amyloid A3 (SAA3) as well as the pro-inflammatory chemokine C-X-C motif chemokine 10 (CXCL10). B. polyandra also significantly suppressed the activation of nucleotide-binding domain like receptor protein 3 (NLRP3) inflammasome and the nuclear factor kB (NF-κB). These results suggest that dietary intake of B. polyandra ameliorates colitis. Such activities of B. polyandra in humans remain to be investigated.